SOCIAL IDENTITY AS A MODERATOR OF THE INFLUENCE OF ENTREPRENEURIAL SELF-EFFICACY ON ENTREPRENEURIAL INTENTION - Salim, Willy; Puspitowati, Ida (Graduate Program of Universitas Tarumanagara, 2025)
Numerous countries have made significant investments in entrepreneurship education and training to foster entrepreneurial activities. This investment is a pivotal element in the efforts of higher education institutions in Indonesia to prepare graduates to become entrepreneurs. The overarching intent of this inquiry is to empirically analyze The ramifications of entrepreneurial self-efficacy (ESE) on entrepreneurial intention (EI) and to evaluate the moderating role of social identity (SI) in this relationship. The study employs a quantitative approach, with the population consisting of students from Tarumanagara University. A purposive sampling method was used, focusing on students majoring in entrepreneurship who enrolled between 2018 and 2022. The research relies on primary data collected directly from participants. The data analysis was executed utilizing Partial Least Squares-Structural Equation Modeling (PLS-SEM). The outcomes demonstrate that ESE exerts a constructive effect on EI, whereas SI does not present a statistically significant moderating role in the relationship between ESE and EI.